The application of organ sound in reverberation measurement in the concert hall of the warsaw academy of music - RAKOWSKI, Andrzej; ERDMAN, Jerzy (Archives of Acoustics, 1977)
Reverberation in the concert hall at the Academy of Music, Warsaw, was determined in the range from 50 to 8000 Hz using the organ as a sound source. The results obtained for 100-4000 Hz do not differ significantly from those obtained from conventional method. To explain the differences in the range of lowest frequencies, the control measurement of the sound decay in low register organ pipes was performed. It was found that the time of sound decay in these pipes may actually be com-parable to the reverberation time of the hall. In the range of highest frequencies the measurement was carried out using a specially selected organ chord to get the sufficient energy in the upper part of the spectrum. The results, are in agreement with those obtained by conventional measurements.